International scientific communication in the context of social networking sites for scientists - Stachowiak, Beata (Torun International Studies, 2015)
In this paper, the author considers the alterations that occurred in the international scientific communication. It is mainly technological development that exerts the influence over these alterations – particularly the emergence of new media. The major part of this paper is dedicated to the issue of the use of social networking sites in scientific communication. In her considerations, the author refers to the world-wide research pertaining to social media in the meantime demonstrating the attitudes of Polish scientists in connection with the former. This paper also contains the results of the research on the attendance to social networking sites of the academics from the Nicolaus Copernicus University with the particular attention paid to Research Gate. The considerations lead to the conclusions that in Poland scientists approach the possibilities offered by social media with the slight skepticism.